Rancang Bangun Pewartaan Injil pada Suku Nias melalui Sanggar Tari - Mendrofa, Eriyani; Suseno, Aji; Anjaya, Carolina Etnasari (STT Iman Jakarta, 2022)
Evangelism in Nias is something that is rarely done considering that Christianity has become the religion of the majority of the community. This religious status was obtained from birth because he followed the religion of his parents. However, this does not guarantee that someone has accepted Jesus as Lord and Savior, there are still churches that have not experienced being born again. That is why evangelism is still done in order to experience the new birth and become a true Christian. From the perspective of the Great Commission, preaching the gospel is a task that must be carried out by every believer. How evangelism is carried out in Nias, how dance culture studios serve as doors for evangelism, as well as the application of the Great Commission through culture are the main topics of discussion in this paper. The method used is a literature study with qualitative analysis, using books and research results on Nias. There are three stages of evangelism carried out, namely: introductions based on friendship (Fahuwusa), associations packaged in the form of dance studio exercises (angowuloa), and gospel preaching (Foturiaigo). The dance studio is an attraction for young Nias people to be willing to spend time together. The meeting will be accompanied by a prayer meeting and spiritual guidance. The purpose of this research can be used as a basis for preaching the gospel to the Nias people with a cultural approach. AbstrakPewartaan Injil di Nias merupakan suatu hal yang jarang dilakukan mengingat agama Kristen telah menjadi agama mayoritas masyarakat. Status agama tersebut diperoleh sejak lahir karena mengikuti agama orangtua. Namun, hal itu tidak menjamin seseorang telah menerima Yesus sebagai Tuhan dan Juruselamat, masih juga terdapat jemaat yang belum mengalami lahir baru. Itulah sebabnya penginjilan tetap dilakukan agar mengalami kelahiran baru dan menjadi Kristen sejati. Dalam perspektif Amanat Agung, pemberitaan Injil merupakan suatu tugas yang harus dilakukan oleh setiap orang percaya. Bagaimana penginjilan dilakukan di Nias, dan seperti apa sanggar budaya tari menjadi pintu penginjilan, serta penerapan Amanat Agung melalui budaya merupakan pokok pembahasan dalam tulisan ini. Metode yang dipakai adalah studi pustaka dengan analisis kualitatif, menggunakan buku-buku dan hasil penelitian tentang Nias. Ada tiga tahap penginjilan yang dilakukan yaitu: perkenalan yang dilandasi dengan dasar persahabatan (fahuwusa), perkumpulan yang dikemas dalam bentuk latihan sanggar tari (angowuloa), dan pemberitaan Injil (Foturiaigo). Sanggar tari merupakan daya tarik bagi anak muda Nias agar bersedia meluangkan waktu berkumpul. Dalam pertemuan tersebut akan disertai dengan persekutuan doa dan bimbingan rohani. Hasil penelitian ini dapat dipakai sebagai dasar untuk memberitakan Injil pada suku Nias dengan pendekatan budaya.